A colloidal palladium activator and its preparation method and chemical copper deposition process
By using the formula of components such as palladium chloride and stannous chloride in the colloid activator, the problems of poor stability and unsatisfactory activation effects of colloid activator are solved, and the colloidal palladium activator with high stability and excellent activation effects are achieved, meeting the chemical copper quality requirements in the field of high-density electronic component manufacturing.
Patent Information
- Application Number
- CN202410640077.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The existing colloid activators have poor stability, poor activation effect, and easy oxidation of Sn2+, which is difficult to meet the quality requirements for chemical copper deposited in the field of high-density electronic component manufacturing.
A novel colloidal palladium activator is used, and its formulation includes palladium chloride, stannous chloride, hydrochloric acid solution, sodium chloride, wetting agent, stabilizer and antioxidant. Through the synergistic action of these components, the stability and active properties of the activator are improved.
The high stability of colloidal palladium activator, excellent activation effect, short copper depositing time and high backlight grade are achieved, and the chemical copper depositing requirements in the field of high-density electronic component manufacturing are met.
Smart Images

Figure BDA0004853031410000121 
Figure BDA0004853031410000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of printed circuit board processing, and in particular to a colloidal palladium activator and a preparation method thereof and a chemical copper deposition process. Background Art
[0002] With the continuous development of printed circuit board technology, the aperture of the via hole is getting smaller and smaller, from the original minimum aperture of 0.3mm to 0.075mm, and the density of the hole is getting higher and higher, from 20,000 to 30,000 holes per board to 150,000 to 350,000 holes per board. In addition, a large number of blind and buried via printed circuit boards (blind via aperture is even smaller to 0.050mm) are mass-produced, which is far from meeting the quality requirements of the traditional hole metallization production method.
[0003] Hole metallization technology is one of the important basic manufacturing technologies for printed circuit boards. It is a process technology for the metal interconnection between the conductive patterns of each layer of the printed circuit board according to regulations to achieve the electrical interconnection of the conductive patterns between the layers of the double-sided board and the multi-layer board. After drilling the printed circuit board substrate, the conductive patterns of each layer are insulated. The insulating hole wall is plated with a layer of conductive metal by chemical plating, and then the deposited conductive copper layer is thickened by copper electroplating to reach the required thickness (generally up to 25um) to meet the needs of electrical connection. The premise for chemical plating to be carried out on the insulating surface is that it must be covered with a layer of catalyst. The role of the activation process in the hole metallization process is to adsorb a dense layer of catalyst on the insulating board surface.
[0004] However, the existing colloidal surfactants still have the following problems: (1) Sn 2+ It is very easy to be oxidized. Once oxidized in the air to form SnOx, it is difficult to remove. (2) Existing colloidal palladium activators often have problems such as poor stability and unsatisfactory activation effect. Summary of the invention
[0005] The purpose of this application is to provide a colloidal palladium activator and a preparation method thereof and a chemical copper deposition process in response to the deficiencies of current technology. The colloidal palladium activator of this application has the advantages of high stability and easy debonding and detachment after activation, excellent activity performance, short copper deposition initiation time, and high backlight level.
[0006] In a first aspect, the present application provides a colloidal palladium activator, which adopts the following technical solution:
[0007] A colloidal palladium activator comprises the following raw materials, measured by mass concentration: 2-3 g / L of palladium chloride, 170-210 g / L of stannous chloride, 150-180 mL / L of hydrochloric acid solution, 170-200 g / L of sodium chloride, 3-5 g / L of wetting agent, 4-7 g / L of stabilizer, 1-3 g / L of antioxidant, and the remainder is deionized water.
[0008] By adopting the above technical scheme, palladium chloride: as one of the main components of the colloidal palladium activator, it plays a role in activating the metal surface and improving the active performance. At the same time, palladium chloride can also form a complex with other raw materials to enhance the stability of colloidal palladium. Stannous chloride: as a reducing agent, stannous chloride can reduce palladium chloride to palladium, increase the content of active ingredients, and improve the activation effect. Hydrochloric acid solution: as a solvent, it can make other raw materials fully mixed, and the chloride ions in hydrochloric acid can also form a complex with palladium chloride to enhance the stability of colloidal palladium. Sodium chloride: sodium chloride can adjust the ion concentration of the colloidal palladium activator, and also acts as a stabilizer to increase stability. Wetting agent: the wetting agent can refine the colloidal particles, increase surface activity, and improve the activation effect. Stabilizer: the stabilizer can inhibit the generation of acid mist, form a stable complex, and enhance the stability of colloidal palladium. Antioxidant: the antioxidant can prevent oxygen from oxidizing Sn 2+ , increasing the stability of colloidal palladium. Through the effects of the above components and their synergistic effects, the colloidal palladium activator can achieve the characteristics of high stability, excellent activity, short copper deposition start-up time and high backlight level. Each component plays an important role in the formula, synergizing with each other to achieve excellent activation effect.
[0009] Preferably, the antioxidant is prepared by mixing glucose and acetaldehyde in a mass ratio of 6:1-2.
[0010] By adopting the above technical solution, the antioxidant is composed of glucose and acetaldehyde, and the mass ratio is 6:1-2. This combination has a synergistic effect in improving the stability of the colloidal palladium activator. Glucose, as a reducing agent, can effectively inhibit the occurrence of oxidation reactions and prevent Sn 2+ Oxidized. Acetaldehyde has good antioxidant properties and can further enhance the stability of the activator. Therefore, the combination of glucose and acetaldehyde can synergize with each other to improve the stability of the colloidal palladium activator and extend its effective use time. The design of this active formula helps to ensure that the activator can maintain high efficiency during use, while reducing the adverse effects that may be caused during storage and transportation.
[0011] Preferably, the stabilizer is prepared by mixing 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide in a mass ratio of 3:1:2-3.
[0012] By adopting the above technical solution, the stabilizer is composed of 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide, and their mass ratio in the formula is 3:1:2-3. The synergistic effect of these stabilizers is very important, which can improve the stability of the colloidal palladium activator and prevent Sn 2+2-aminopyridine and 2-amino-4-methylpyridine are good antioxidants, which can effectively prevent Sn in the activator from being oxidized. 2+ is oxidized, thus extending the service life of the activator. At the same time, methacrylamide can react with Sn 2+ The formation of a stable complex further enhances the stability of the colloidal palladium activator. Therefore, the synergistic effect of these three stabilizers in the formula can effectively improve the stability and activity performance of the colloidal palladium activator, making it have excellent activation effect and long-term stability.
[0013] Preferably, the wetting agent is prepared by mixing polyethoxybutylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl)aniline in a mass ratio of 6:1:2-3.
[0014] By adopting the above technical scheme, the role of the wetting agent in the colloidal palladium activator is to make the colloidal particles more refined and improve the activity of the activator. In the present application, the formula of the wetting agent includes polyethoxy butylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl) aniline, and their mass ratio is 6:1:2-3. Polyethoxy butylthiophene sulfonic acid has good wetting properties, and the activator can be better contacted with the substrate, thereby improving the activation efficiency. 3-aminophenol has certain reducibility, and the reducing power of the activator can be enhanced, which helps to improve the activity of the activator. And 2-(5-oxazolyl) aniline can enhance the dispersibility of the wetting agent, so that it is more evenly distributed in the activator, thereby further improving the performance of the activator. These three components work together, and more active sites can be produced on the activator surface, and the activity and stability of the activator are improved, thereby achieving a more efficient activation effect.
[0015] Preferably, the mass fraction of hydrogen chloride in the hydrochloric acid solution is 36%-38%.
[0016] In a second aspect, the present application provides a method for preparing a colloidal palladium activator, using the following technical solution:
[0017] As a general technical concept, the present application also provides a method for preparing the above-mentioned colloidal palladium activator, comprising the following steps: S61, dissolving palladium chloride in one-half hydrochloric acid solution to prepare liquid A according to the formula dosage;
[0018] S62, dissolving stannous chloride in half of hydrochloric acid solution to prepare solution B according to a molar ratio of stannous chloride to palladium chloride of 2:1;
[0019] S63, according to the formula dosage, sodium chloride, remaining stannous chloride, wetting agent, stabilizer, antioxidant and deionized water are stirred and mixed to prepare liquid C;
[0020] S64, add solution B to solution A, slowly stir at 40°C for 1-2 hours, until the solution turns brown to obtain solution D;
[0021] S65. Rapidly add liquid D into liquid C and mix evenly. Continue stirring for 30-60 minutes, then heat to 50-70°C and keep warm for 3-6 hours to obtain a colloidal palladium activator.
[0022] In a third aspect, the present application provides a chemical copper deposition process, which adopts the following technical solution:
[0023] As a general technical concept, the present application also provides a chemical copper plating process, comprising the following steps: a porous and dense PBC board with a small pore size → bulking treatment → desmearing → neutralization → degreasing → acid etching → activation → chemical copper plating;
[0024] The electroless copper plating solution comprises the following raw materials by mass concentration: 5-8 g / L copper sulfate pentahydrate, 18-22 g / L formaldehyde, 2-3 g / L 1-benzyl-3-methylimidazolinol, 0.01-0.03 g / L tetrahydroxypropylethylenediamine, 30-35 g / L complexing agent, 20-25 g / L sodium carbonate, 0.01-0.03 g / L stabilizer, 0.005-0.008 g / L surfactant, and the remainder is deionized water; the activated active solution contains the above-mentioned colloidal palladium activator.
[0025] By adopting the above technical scheme, copper sulfate pentahydrate: as the main copper source of the copper plating solution, it provides copper ions and is the basis for copper deposition. Formaldehyde: as a reducing agent, it helps to reduce copper ions into solid metal copper and promote the copper deposition reaction. 1-Benzyl-3-methylimidazolinol: as an additive, it can improve the deposition rate and uniformity of copper and help to obtain a dense and uniform copper plating layer. Tetrahydroxypropylethylenediamine: as a buffer, it helps to maintain the pH value of the plating solution and improve the stability of the plating solution. Complexing agent: helps to form a stable complex, protect copper ions from other impurities, and improve deposition efficiency. Sodium carbonate: used to adjust the pH value of the plating solution, and at the same time can improve the conductivity of the plating solution and promote copper deposition. Stabilizer: helps to reduce harmful oxidation reactions, maintain the stability of the plating solution, and improve the controllability of the copper plating process. Surfactant: improves the wettability of the plating solution, helps to deposit a copper layer uniformly, and improves the adhesion of the coating. These components work synergistically with each other to promote the copper deposition process. Formaldehyde and 1-benzyl-3-methylimidazolinol accelerate the copper deposition reaction, the complexing agent and stabilizer maintain the stability of the plating solution, and the sodium carbonate and surfactant improve the uniformity and adhesion of the deposition. The addition of colloidal palladium activator also helps to form better copper deposition on the PBC board, thereby achieving high-quality chemical copper plating. The synergistic effect of these components makes the process have the advantages of good stability, fast deposition speed, dense and uniform copper plating, and good coating adhesion.
[0026] Preferably, the complexing agent is prepared by mixing potassium sodium tartrate and tetrahydroxypropylethylenediamine in a mass ratio of 4:1.
[0027] By adopting the above technical scheme, potassium sodium tartrate: potassium sodium tartrate is usually used as a complexing agent in chemical copper plating, and its main function is to form a stable complex with copper ions, thereby preventing copper from having adverse reactions in the plating solution, improving the stability of the plating solution, and promoting the deposition of copper. Tetrahydroxypropyl ethylenediamine: Tetrahydroxypropyl ethylenediamine, as a buffer in the plating solution, can help maintain a suitable pH value, improve the stability of the plating solution, and prevent the pH value from being too high or too low from having a negative impact on the copper plating process. After mixing potassium sodium tartrate and tetrahydroxypropyl ethylenediamine, the complexing reaction can be enhanced, the copper ions can be better protected from the influence of other impurities, and the deposition efficiency can be improved. The combined action of the two can make the plating solution more stable, reduce the oxidation reaction in the plating solution, improve the controllability of the operation, and ensure the smooth progress of the copper plating process. The synergistic effect of potassium sodium tartrate and tetrahydroxypropyl ethylenediamine can promote the formation of a uniform and dense copper plating layer, ensure the quality of the deposited layer, and enhance the adhesion of the coating. Therefore, the complexing agent prepared by mixing potassium sodium tartrate and tetrahydroxypropylethylenediamine plays an important role in the present application, and synergistically improves the efficiency and quality of chemical copper plating.
[0028] Preferably, the stabilizer is prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea in a mass ratio of 3:2:0.15.
[0029] By adopting the above technical scheme, 2,2'-bipyridine as a stabilizer plays an anti-oxidation role in the chemical copper plating process, can effectively inhibit the oxidation reaction in the plating solution, extend the effective service life of the plating solution, and improve the quality and flatness of the deposited layer. Potassium hexacyanoferrate exists as a complexing agent in the stabilizer, can combine with metal ions to form a complex, stabilize the metal ions in the plating solution, reduce its reaction with other substances, and improve the uniformity and glossiness of the coating. The role of allylthiourea in the stabilizer is mainly as a surfactant, which can promote the contact between the liquid and the solid, improve the wettability of the plating solution, and help to deposit the copper layer uniformly and meticulously. After mixing, these three components can synergize with each other and jointly play the following effects: Improve the stability of the plating solution: The stabilizer maintains the stability of the copper plating solution by inhibiting oxidation reactions, improving the complexing effect and adjusting the properties of the liquid, making the copper plating process more controllable. Promote deposition speed and uniformity: The synergistic effect of these three components helps to promote the deposition speed, while improving the stability and fluidity of the metal ions in the plating solution, which is conducive to obtaining a dense and uniform copper coating. Improve the adhesion of the coating: The components in the stabilizer work together to promote the bonding of the deposited copper layer with the base material, improve the adhesion of the coating, prevent problems such as cracking or falling off, and ensure the acquisition of high-quality copper coating. Therefore, the stabilizer prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea plays an important role in this application, synergistically improving the efficiency and quality of chemical copper plating.
[0030] Preferably, the surfactant is prepared by mixing polyvinyl pyrrolidone and dodecylbenzene sulfonic acid in a mass ratio of 6:1.
[0031] By adopting the above technical scheme, the surfactant plays an important role in the chemical copper plating process, helps to adjust the surface tension and wettability of the plating solution, promotes the contact between the liquid and the solid surface, and thus affects the uniformity, density and adhesion of the deposited copper layer. Polyvinyl pyrrolidone is a polymer surfactant that plays a role in stabilizing the liquid properties and reducing the surface tension in the plating solution. It can improve the uniformity and glossiness of the deposited copper layer, and at the same time help to reduce the generation of bubbles and improve the deposition quality. Dodecylbenzene sulfonic acid is an organic surfactant with good wettability and dispersibility, which can make the plating solution more easily adhere to the surface of the substrate, promote the deposition of copper ions on the substrate, and improve the uniformity and density of the coating. The mixed surfactant can reduce the surface tension between the liquid and the substrate, increase the contact area of the deposited copper layer, and thus improve the uniformity and integrity of the copper deposition. The presence of the surfactant can promote the uniform transport and dispersion of metal ions in the plating solution, help to increase the deposition rate and reduce the defect rate. The surfactant helps to form a uniform deposition layer on the surface of the substrate, improve the bonding force between the coating and the substrate, and enhance the adhesion and corrosion resistance of the copper coating.
[0032] In summary, the beneficial technical effects of this application are:
[0033] 1. High stability: By adding antioxidants and stabilizers to the formula, the activator can be effectively prevented from being damaged by oxidation and other adverse factors, thereby improving the stability of colloidal palladium. This means that the activator is more durable and reliable during use, which is conducive to increasing its service life.
[0034] 2. Easy to dissolve and detach: After the activated colloidal palladium is bonded to the substrate, it is easy to solidify and easy to remove in the subsequent process steps. This advantage can improve the efficiency of the process and the quality of the product and reduce problems in the production process.
[0035] 3. Excellent active performance: Through the careful design of the formula, wetting agents and other ingredients can make the colloidal particles more refined and improve the activity of the activator. This means that during the activation process, the contact area is increased, the reaction rate is increased, and the active performance is optimized.
[0036] 4. Short copper deposition start-up time: The formula and performance design of the activator reduces the copper deposition start-up time, that is, the activation speed is faster. This is conducive to improving efficiency and shortening production cycles during the production process.
[0037] 5. High backlight level: A sufficiently high backlight level means that the activated colloidal palladium can provide better detection results under certain conditions, and can meet the requirements of chemical copper plating of PBC printed circuit boards with densely porous and small pore sizes. It is suitable for the field of high-density electronic component manufacturing and has broad application prospects.
[0038] 6. Good plating solution stability: The chemical copper plating solution has good stability, can be maintained within a suitable working range for a long time, is not prone to precipitation or stratification, and ensures the continuity and stability of the deposition process.
[0039] 7. Excellent plating quality: The copper plating deposited by this process is dense, uniform, smooth, with high surface flatness and strong adhesion, which improves the performance and reliability of printed circuit boards. DETAILED DESCRIPTION
[0040] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Example 1
[0042] A colloidal palladium activator comprises the following raw materials, measured by mass concentration: 2 g / L palladium chloride, 170 g / L stannous chloride, 150 mL / L hydrochloric acid solution, 170 g / L sodium chloride, 3 g / L wetting agent, 4 g / L stabilizer, 1 g / L antioxidant, and the remainder being deionized water. The antioxidant is prepared by mixing glucose and acetaldehyde in a mass ratio of 6:1, the stabilizer is prepared by mixing 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide in a mass ratio of 3:1:2, the wetting agent is prepared by mixing polyethoxybutylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl)aniline in a mass ratio of 6:1:2, and the mass fraction of hydrogen chloride in the hydrochloric acid solution is 36%.
[0043] The preparation method of the colloidal palladium activator comprises the following steps:
[0044] S61. According to the dosage of the formula, dissolve palladium chloride in one-half hydrochloric acid solution to prepare liquid A;
[0045] S62, dissolving stannous chloride in half of hydrochloric acid solution to prepare solution B according to a molar ratio of stannous chloride to palladium chloride of 2:1;
[0046] S63, according to the formula dosage, sodium chloride, remaining stannous chloride, wetting agent, stabilizer, antioxidant and deionized water are stirred and mixed to prepare liquid C;
[0047] S64, add solution B to solution A, slowly stir at 40°C for 1 hour, and the solution turns brown to obtain solution D;
[0048] S65. Rapidly add liquid D into liquid C and mix evenly. After continuous stirring for 30 minutes, heat to 50°C and keep warm for 6 hours to obtain a colloidal palladium activator.
[0049] Example 2
[0050] A colloidal palladium activator comprises the following raw materials, measured by mass concentration: 3 g / L palladium chloride, 210 g / L stannous chloride, 180 mL / L hydrochloric acid solution, 200 g / L sodium chloride, 5 g / L wetting agent, 7 g / L stabilizer, 3 g / L antioxidant, and the remainder is deionized water, wherein the antioxidant is prepared by mixing glucose and acetaldehyde in a mass ratio of 6:2, the stabilizer is prepared by mixing 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide in a mass ratio of 3:1:3, the wetting agent is prepared by mixing polyethoxybutylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl)aniline in a mass ratio of 6:1:3, and the mass fraction of hydrogen chloride in the hydrochloric acid solution is 38%.
[0051] The preparation method of the colloidal palladium activator comprises the following steps:
[0052] S61. According to the dosage of the formula, dissolve palladium chloride in one-half hydrochloric acid solution to prepare liquid A;
[0053] S62, dissolving stannous chloride in half of hydrochloric acid solution to prepare solution B according to a molar ratio of stannous chloride to palladium chloride of 2:1;
[0054] S63, according to the formula dosage, sodium chloride, remaining stannous chloride, wetting agent, stabilizer, antioxidant and deionized water are stirred and mixed to prepare liquid C;
[0055] S64, add solution B to solution A, slowly stir at 40°C for 2 hours, and the solution turns brown to obtain solution D;
[0056] S65. Rapidly add liquid D into liquid C and mix evenly. After continuous stirring for 60 minutes, heat to 70°C and keep warm for 3 hours to obtain a colloidal palladium activator.
[0057] Example 3
[0058] A colloidal palladium activator comprises the following raw materials, measured by mass concentration: 2.5 g / L palladium chloride, 190 g / L stannous chloride, 160 mL / L hydrochloric acid solution, 180 g / L sodium chloride, 4 g / L wetting agent, 5.5 g / L stabilizer, 2 g / L antioxidant, and the remainder is deionized water, wherein the antioxidant is prepared by mixing glucose and acetaldehyde in a mass ratio of 6:1.5, the stabilizer is prepared by mixing 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide in a mass ratio of 3:1:2.5, the wetting agent is prepared by mixing polyethoxybutylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl)aniline in a mass ratio of 6:1:2.5, and the mass fraction of hydrogen chloride in the hydrochloric acid solution is 37%.
[0059] The preparation method of the colloidal palladium activator comprises the following steps:
[0060] S61. According to the dosage of the formula, dissolve palladium chloride in one-half hydrochloric acid solution to prepare liquid A;
[0061] S62, dissolving stannous chloride in half of hydrochloric acid solution to prepare solution B according to a molar ratio of stannous chloride to palladium chloride of 2:1;
[0062] S63, according to the formula dosage, sodium chloride, remaining stannous chloride, wetting agent, stabilizer, antioxidant and deionized water are stirred and mixed to prepare liquid C;
[0063] S64, add solution B to solution A, slowly stir at 40°C for 1.5 hours, until the solution turns brown to obtain solution D;
[0064] S65. Rapidly add solution D into solution C and mix evenly. After continuous stirring for 50 minutes, heat to 60°C and keep warm for 4.5 hours to obtain a colloidal palladium activator.
[0065] Comparative Example 1
[0066] Same as Example 3, except that the antioxidant is glucose.
[0067] Comparative Example 2
[0068] The same as Example 3, except that the antioxidant is acetaldehyde.
[0069] Comparative Example 3
[0070] The same as Example 3, except that the stabilizer is 2-aminopyridine.
[0071] Comparative Example 4
[0072] The same as Example 3, except that the stabilizer is 2-amino-4-methylpyridine.
[0073] Comparative Example 5
[0074] The same as Example 3, except that the stabilizer is methacrylamide.
[0075] Comparative Example 6
[0076] The same as Example 3, except that the wetting agent is polyethoxybutylthiophene sulfonic acid.
[0077] Comparative Example 7
[0078] The same as Example 3, except that the wetting agent is 3-aminophenol.
[0079] Comparative Example 8
[0080] The same as Example 3, except that the wetting agent is 2-(5-oxazolyl)aniline.
[0081] Example 4 Chemical copper plating solution
[0082] The electroless copper plating solution comprises the following raw materials, measured by mass concentration: 5 g / L copper sulfate pentahydrate, 18 g / L formaldehyde, 2 g / L 1-benzyl-3-methylimidazolinol, 0.01 g / L tetrahydroxypropylethylenediamine, 30 g / L complexing agent, 20 g / L sodium carbonate, 0.01 g / L stabilizer, 0.005 g / L surfactant, and the remainder is deionized water, wherein the complexing agent is prepared by mixing potassium sodium tartrate and tetrahydroxypropylethylenediamine in a mass ratio of 4:1, the stabilizer is prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea in a mass ratio of 3:2:0.15, and the surfactant is prepared by mixing polyvinyl pyrrolidone and dodecylbenzenesulfonic acid in a mass ratio of 6:1.
[0083] Example 5 Chemical copper plating solution
[0084] The electroless copper plating solution comprises the following raw materials, measured by mass concentration: 8 g / L copper sulfate pentahydrate, 22 g / L formaldehyde, 3 g / L 1-benzyl-3-methylimidazolinol, 0.03 g / L tetrahydroxypropylethylenediamine, 35 g / L complexing agent, 25 g / L sodium carbonate, 0.03 g / L stabilizer, 0.008 g / L surfactant, and the remainder being deionized water. The complexing agent is prepared by mixing potassium sodium tartrate and tetrahydroxypropylethylenediamine in a mass ratio of 4:1, the stabilizer is prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea in a mass ratio of 3:2:0.15, and the surfactant is prepared by mixing polyvinylpyrrolidone and dodecylbenzenesulfonic acid in a mass ratio of 6:1.
[0085] Example 6 Chemical copper plating solution
[0086] The electroless copper plating solution comprises the following raw materials, measured by mass concentration: 7 g / L copper sulfate pentahydrate, 20 g / L formaldehyde, 2.5 g / L 1-benzyl-3-methylimidazolinol, 0.02 g / L tetrahydroxypropylethylenediamine, 33 g / L complexing agent, 23 g / L sodium carbonate, 0.02 g / L stabilizer, 0.007 g / L surfactant, and the remainder is deionized water, wherein the complexing agent is prepared by mixing potassium sodium tartrate and tetrahydroxypropylethylenediamine in a mass ratio of 4:1, the stabilizer is prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea in a mass ratio of 3:2:0.15, and the surfactant is prepared by mixing polyvinyl pyrrolidone and dodecylbenzenesulfonic acid in a mass ratio of 6:1.
[0087] Comparative Example 9 Chemical Copper Plating Solution
[0088] The same as Example 6, except that the stabilizer is 2,2'-bipyridine.
[0089] Comparative Example 10 Chemical copper plating solution
[0090] The same as Example 6, except that the stabilizer is potassium hexacyanoferrate.
[0091] Comparative Example 11 Chemical copper plating solution
[0092] The same as Example 6, except that the stabilizer is allylthiourea.
[0093] Comparative Example 12 Chemical copper plating solution
[0094] The same as Example 6, except that the complexing agent is potassium sodium tartrate.
[0095] Comparative Example 13 Chemical copper plating solution
[0096] The same as Example 6, except that the complexing agent is tetrahydroxypropylethylenediamine.
[0097] Comparative Example 14 Chemical copper plating solution
[0098] Same as Example 6, except that the surfactant is polyvinyl pyrrolidone.
[0099] Comparative Example 15 Chemical copper plating solution
[0100] The same as Example 6, except that the surfactant is dodecylbenzenesulfonic acid.
[0101] Application Example 1: A Chemical Copper Plating Process
[0102] A chemical copper plating process, comprising the following steps: a porous and dense PBC board with a small pore size → bulking → removing glue residue → neutralization → degreasing → acid etching → activation → chemical copper plating;
[0103] 1. PBC board with dense pores and small pore size: board thickness 1.2mm, minimum through hole diameter 0.225mm, through hole thickness-to-diameter ratio 5.31; blind hole depth 60μm, pore diameter 100μm;
[0104] 2. Swelling treatment: Each circuit board is expanded in 240 liters of expansion treatment liquid at 70℃ for 6 minutes; the expansion treatment liquid is an aqueous solution containing 20% W-601 and 30g / L sodium hydroxide. (The expansion treatment liquid is selected from W-601 of Huizhou Ronganda Chemical Co., Ltd.); 3. Then rinse the circuit board in room temperature water for 1 minute at room temperature;
[0105] 4. Remove glue residue: Then use an alkaline glue remover containing 55g / L potassium permanganate and 55g / L NaOH on the through holes of each circuit board and treat it at 75℃ for 13min;
[0106] 5. Rinse the circuit board in cold tap water at room temperature for 1 minute;
[0107] 6. Neutralization: At 40°C, the circuit board is treated in a neutralizer containing 20% W-203 and 30ml / L H2SO4 for 7 minutes. The neutralizer is selected from W-203 of Huizhou Ronganda Chemical Co., Ltd.;
[0108] 7. Rinse the circuit board in water at room temperature for 1 minute;
[0109] 8. Degreasing: At 60°C, use a degreasing agent: 10% CH-616, 90% deionized water (selected from CH-616 of Huizhou Rong'anda Chemical Co., Ltd.) to treat the circuit board for 7 minutes;
[0110] 9. Rinse the circuit board in water at room temperature for 1 minute;
[0111] 10. Acid etching: At 60°C, use an acid etching solution: 10% CH-626, 90% deionized water (selected from Huizhou Ronganda Chemical Co., Ltd. using pre-soak) to treat the circuit board for 7 minutes;
[0112] 11. Rinse the circuit board in water at room temperature for 1 minute;
[0113] 12. Pre-soak: At room temperature 25°C, use pre-soak agent: 170g / L pre-soak salt CH-628R, 37ml / L hydrochloric acid (37% AR grade) (selected from CH-628R of Huizhou Ronganda Chemical Co., Ltd.) to treat the circuit board for 90s;
[0114] 13. Rinse the circuit board in water at room temperature for 1 minute;
[0115] 14. Activation: using colloidal palladium activator, perfusing the circuit board at 42° C. for 6 minutes, wherein the concentration of the colloidal palladium activator is 0.8%, and the colloidal palladium activator is the colloidal palladium activator of Example 1;
[0116] 15. Rinse the circuit board in water at room temperature for 1 minute;
[0117] 16. Acceleration: The circuit board was treated in an accelerator for 2.5 min at 40°C. The accelerator was CH-648A / B from Huizhou Ronganda Chemical Co., Ltd.
[0118] 17. Soak the circuit board in water at room temperature for 1 minute;
[0119] 18. Chemical copper plating: chemically copper-plating the circuit board in a chemical copper plating solution at 35° C. for 15 min, wherein the chemical copper plating solution is the plating solution of Example 6;
[0120] 19. After chemical copper plating, rinse the substrate in room temperature water for 1 min at room temperature to obtain a chemical copper plating layer.
[0121] Application Example 2: A Chemical Copper Plating Process
[0122] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Example 2.
[0123] Application Example 3: A Chemical Copper Plating Process
[0124] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Example 3.
[0125] Application Example 4: A Chemical Copper Plating Process
[0126] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 1.
[0127] Application Example 5: A Chemical Copper Plating Process
[0128] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 2.
[0129] Application Example 6: A Chemical Copper Plating Process
[0130] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 3.
[0131] Application Example 7: A Chemical Copper Plating Process
[0132] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 4.
[0133] Application Example 8: A Chemical Copper Plating Process
[0134] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 5.
[0135] Application Example 9: A Chemical Copper Plating Process
[0136] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 6.
[0137] Application Example 10: A Chemical Copper Plating Process
[0138] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 7.
[0139] Application Example 11 A Chemical Copper Plating Process
[0140] The same as Application Example 1, except that the colloidal palladium activator is the colloidal palladium activator of Comparative Example 8.
[0141] Application Example 12: A Chemical Copper Plating Process
[0142] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Example 4.
[0143] Application Example 13: A Chemical Copper Plating Process
[0144] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Example 5.
[0145] Application Example 14: A Chemical Copper Plating Process
[0146] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Example 6.
[0147] Application Example 15: A Chemical Copper Plating Process
[0148] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 9.
[0149] Application Example 16: A Chemical Copper Plating Process
[0150] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 10.
[0151] Application Example 16: A Chemical Copper Plating Process
[0152] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 11.
[0153] Application Example 18: A Chemical Copper Plating Process
[0154] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 12.
[0155] Application Example 19: A Chemical Copper Plating Process
[0156] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 13.
[0157] Application Example 20: A Chemical Copper Plating Process
[0158] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 14.
[0159] Application Example 21 A Chemical Copper Plating Process
[0160] The same as Application Example 3, except that the chemical copper plating solution is the plating solution of Comparative Example 15.
[0161] 1. Performance Test
[0162] The chemically plated copper layers prepared in each application example were subjected to the following tests, and the test results are shown in Table 1.
[0163] 1. Sedimentation rate test: The sedimentation rate is determined by the weight gain method, and the calculation formula is as follows:
[0164] v=(m1-m0)×10000 / (ρ×A×t);
[0165] Where v is the deposition rate, μm / h; m0 and m1 are the mass of the plated part before and after plating, respectively, g; ρ is the relative density of copper, 8.93 g / cm 3 ; A is the surface area of the plated part, cm 2 ; t is the plating time, h;
[0166] 2. Adhesion test: Use the 100-grid test method, use 3M 610 tape to tear, no peeling is OK, and peeling is NG;
[0167] 3. Test of the stability of electroless copper plating solution: Since it takes a long time for the plating solution to decompose naturally, in order to shorten the experimental time, an accelerated method is generally used. This application uses a palladium chloride accelerated test to test the stability of the plating solution: add 15mL PdCl2 (0.18g / L) to 50mL of the plating solution at a temperature of 60°C, and record the decomposition time of the plating solution, that is, the time required to produce a large amount of red copper powder and hydrogen;
[0168] 4. Backlight level: After copper deposition, place the test piece in a slicer and cut it. Grind it with a grinder to grind off 1 / 2 of the hole diameter of the slice, and grind the other side of the slice to about 2mm from the edge of the hole. After grinding, wipe the copper chips and glue residue in the hole with a soft cloth, and use a microscope to magnify 50 times to detect the condition in the hole. Use the backlight principle (if the chemical copper is deposited evenly, the lower light cannot be seen through, the entire hole wall appears completely black, and the backlight level is 10) to check the uniformity of chemical copper deposition on the hole wall of each hole. The backlight level is required to reach above level 8.
[0169] 5. Reaction activity: The time from when the test piece is immersed in the chemical copper plating solution to the generation of the first bubble on the surface of the test piece is the initiation time. The shorter the initiation time, the stronger the activity of the activation solution.
[0170] 2. Stability test of colloidal palladium activator
[0171] The colloidal palladium activators prepared in Example 1, Example 3 and Comparative Examples 1 to Comparative Examples 8 were inflated with an air pump at room temperature (25° C.) overnight and then subjected to performance testing the next day to observe whether the colloidal palladium activators were decomposed or their performance deteriorated. The results are shown in Table 2.
[0172] Table 1 Performance test
[0173]
[0174]
[0175] Table 2 Colloidal palladium activator stability test
[0176] project Decomposition time / h Example 1 90 Example 2 90 Example 3 91 Comparative Example 1 73 Comparative Example 2 71 Comparative Example 3 72 Comparative Example 4 63 Comparative Example 5 60 Comparative Example 6 66 Comparative Example 7 78 Comparative Example 8 79
[0177] Analyzing the data in Tables 1 and 2, we can see that:
[0178] 1) The colloidal palladium activator prepared in Examples 1 to 3 has high stability and is easy to dissolve and detach after activation, and has the advantages of excellent activity performance, short copper deposition initiation time, and high backlight level.
[0179] 2) The comparative analysis of the performance of the colloidal palladium activator prepared in combination with Example 3 and Comparative Examples 1-2 shows that the antioxidant is prepared by mixing glucose and acetaldehyde in a mass ratio of 6:1.5, and the synergistic effect between them is utilized to improve the stability of the colloidal palladium activator and extend its effective use time. The design of this active formula helps to ensure that the activator can maintain high performance during use, while reducing the adverse effects that may be caused during storage and transportation.
[0180] 3) The performance comparison analysis of the colloidal palladium activator prepared in combination with Example 3 and Comparative Examples 3 to Comparative Examples 5 shows that the stabilizer is prepared by mixing 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide in a mass ratio of 3:1:2.5. The synergistic effect of these stabilizers is very important, which can improve the stability of the colloidal palladium activator and prevent Sn 2+ 2-aminopyridine and 2-amino-4-methylpyridine are good antioxidants, which can effectively prevent Sn in the activator from being oxidized. 2+ is oxidized, thus extending the service life of the activator. At the same time, methacrylamide can react with Sn 2+ The formation of a stable complex further enhances the stability of the colloidal palladium activator. Therefore, the synergistic effect of these three stabilizers in the formula can effectively improve the stability and activity performance of the colloidal palladium activator, making it have excellent activation effect and long-term stability.
[0181] 4) The performance comparison analysis of the colloidal palladium activator prepared in combination with Example 3 and Comparative Examples 6-8 shows that the wetting agent is prepared by mixing polyethoxybutylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl)aniline in a mass ratio of 6:1:2.5. The role of the wetting agent in the colloidal palladium activator is to make the colloidal particles more refined and improve the activity of the activator. These three components work together to produce more active sites on the surface of the activator, improve the activity and stability of the activator, and thus achieve a more efficient activation effect.
[0182] 5) The performance comparison analysis of the chemical copper plating solution prepared in combination with Example 6 and Comparative Examples 9-11 shows that the stabilizer is prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea in a mass ratio of 3:2:0.15. By utilizing the synergistic effect between them, the three components can work together after mixing to jointly exert the following effects: Improve the stability of the plating solution: The stabilizer maintains the stability of the copper plating solution by inhibiting oxidation reactions, improving the complexing effect and adjusting the properties of the liquid, making the copper plating process more controllable. Promote deposition rate and uniformity: The synergistic effect of the three components helps to promote the deposition rate, while improving the stability and fluidity of the metal ions in the plating solution, which is conducive to obtaining a dense and uniform copper coating. Improve the adhesion of the coating: The components in the stabilizer work together to promote the combination of the deposited copper layer and the base material, improve the adhesion of the coating, prevent problems such as cracking or falling off, and ensure that a high-quality copper coating is obtained.
[0183] 6) The performance comparison analysis of the chemical copper plating solution prepared in combination with Example 6 and Comparative Examples 12-13 shows that the complexing agent is prepared by mixing potassium sodium tartrate and tetrahydroxypropyl ethylenediamine in a mass ratio of 4:1. The two can make the plating solution more stable, reduce the oxidation reaction in the plating solution, improve the controllability of the operation, and ensure the smooth progress of the copper plating process. The synergistic effect of potassium sodium tartrate and tetrahydroxypropyl ethylenediamine can promote the formation of a uniform and dense copper coating, ensure the quality of the deposited layer, and enhance the adhesion of the coating.
[0184] 7) The performance comparison analysis of the chemical copper plating solution prepared in combination with Example 6 and Comparative Examples 14-15 shows that the surfactant is prepared by mixing polyvinyl pyrrolidone and dodecylbenzene sulfonic acid in a mass ratio of 6:1. By utilizing the synergistic effect between them, the surfactant plays an important role in the chemical copper plating process, helps to adjust the surface tension and wettability of the plating solution, promotes the contact between the liquid and the solid surface, thereby affecting the uniformity, density and adhesion of the deposited copper layer.
[0185] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A colloidal palladium activator, characterized in that The preparation raw materials include the following according to mass concentration: 2-3 g / L of palladium chloride, 170-210 g / L of stannous chloride, 150-180 mL / L of hydrochloric acid solution, 170-200 g / L of sodium chloride, 3-5 g / L of wetting agent, 4-7 g / L of stabilizer, 1-3 g / L of antioxidant, and the rest is deionized water; The antioxidant is prepared by mixing glucose and acetaldehyde in a mass ratio of 6:1-2; The stabilizer is prepared by mixing 2-aminopyridine, 2-amino-4-methylpyridine and methacrylamide in a mass ratio of 3:1:2-3; the wetting agent is prepared by mixing polyethoxybutylthiophene sulfonic acid, 3-aminophenol and 2-(5-oxazolyl)aniline in a mass ratio of 6:1:2-3; The preparation method of the colloidal palladium activator comprises the following steps: S61. Dissolve palladium chloride in half of hydrochloric acid solution to prepare solution A according to the formula dosage; S62, dissolving stannous chloride in half of hydrochloric acid solution to prepare solution B according to a molar ratio of stannous chloride to palladium chloride of 2:1; S63, according to the dosage of the formula, sodium chloride, the remaining stannous chloride, the wetting agent, the stabilizer, the antioxidant and the deionized water are stirred and mixed to prepare liquid C; S64, add solution B to solution A, slowly stir at 40°C for 1-2 hours, until the solution turns brown to obtain solution D; S65. Rapidly add liquid D into liquid C and mix evenly. Continue stirring for 30-60 minutes, then heat to 50-70°C and keep warm for 3-6 hours to obtain a colloidal palladium activator.
2. A colloidal palladium activator according to claim 1, characterized in that: The mass fraction of hydrogen chloride in the hydrochloric acid solution is 36%-38%.
3. A chemical copper deposition process, characterized in that: The following steps are included: PCB board with dense pores and small pore size → bulking → desmearing → neutralization → degreasing → acid etching → activation → chemical copper plating; Wherein, the electroless copper plating solution comprises the following raw materials by mass concentration: 5-8 g / L copper sulfate pentahydrate, 18-22 g / L formaldehyde, 2-3 g / L 1-benzyl-3-methylimidazolinol, 0.01-0.03 g / L tetrahydroxypropylethylenediamine, 30-35 g / L complexing agent, 20-25 g / L sodium carbonate, 0.01-0.03 g / L stabilizer, 0.005-0.008 g / L surfactant, and the remainder is deionized water; the active solution of the activation process contains the colloidal palladium activator described in any one of claims 1-2; The complexing agent is prepared by mixing potassium sodium tartrate and tetrahydroxypropylethylenediamine in a mass ratio of 4:1; The stabilizer is prepared by mixing 2,2'-bipyridine, potassium hexacyanoferrate and allylthiourea in a mass ratio of 3:2:0.15; The surfactant is prepared by mixing polyvinyl pyrrolidone and dodecylbenzene sulfonic acid in a mass ratio of 6:1.
Citation Information
Patent Citations
Electroless copper plating activating solution and preparation method thereof
CN110670050A
Colloid palladium activating solution and preparation method thereof
CN115928054A
High-stability colloid palladium active agent of sulfuric acid system and preparation method of high-stability colloid palladium active agent
CN116695102A